2021
DOI: 10.1111/puar.13438
|View full text |Cite
|
Sign up to set email alerts
|

Social Public Purchasing: Addressing a Critical Void in Public Purchasing Research

Abstract: Since governments are the largest buyers globally, they have enormous purchasing power. Government purchasing, therefore, has potential to be leveraged to improve social outcomes, such as helping disadvantaged communities, ensuring labor rights, and minimizing negative environmental impacts. However, as yet, there is little understanding about social public purchasing research in the field of public administration. We provide a theoretical framework for organizing research around social public purchasing. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 125 publications
(155 reference statements)
0
10
0
Order By: Relevance
“…Although not perfect, government quasi-markets-like all markets-respond to demand and do so efficiently. In this sense, agencies could use the nature of markets to generate demand for products that minimize the negative imprint on the environment and improve social equity (Hafsa et al, 2021). Using purchasing and contracting to achieve social and environmental policy goals is known as sustainable public procurement (Alkadry et al, 2019).…”
Section: Sustainabilitymentioning
confidence: 99%
“…Although not perfect, government quasi-markets-like all markets-respond to demand and do so efficiently. In this sense, agencies could use the nature of markets to generate demand for products that minimize the negative imprint on the environment and improve social equity (Hafsa et al, 2021). Using purchasing and contracting to achieve social and environmental policy goals is known as sustainable public procurement (Alkadry et al, 2019).…”
Section: Sustainabilitymentioning
confidence: 99%
“…Previous research on correlates of attitudes of administrators of public institutions toward public participation has also found that such attitudes are strongly associated with administrators' perceptions regarding the input legitimacy of participatory processes, namely participants' turnout and their representativeness of wider communities (Migchelbrink & Van de Walle, 2020, 2021). While increasing the number of participants can certainly reflect positive elements of public participation, a rhetoric that presents it as a solution to marginalized citizens' exclusion from participative processes veils the fact that such exclusion can persist if the increase in attendance is not actively accompanied by ensuring that attendees include citizens from the lower ends of the social and epistemic hierarchy (Hafsa et al, 2021; McCollum, 2012). Another example thereof can be taken from CECs' alternative suggestion that a better indicator of inclusive public participation would be ensuring that citizens understand municipal plans and their implications.…”
Section: Discussionmentioning
confidence: 99%
“…Government procurement of public services is a policy practice implemented to improve governance levels and foster the development of social organizations (Hafsa et al, 2022). According to Rodriguez‐Plesa et al (2022), sustainable public procurement (SPP) presents a viable approach for local governments to tackle these concerns.…”
Section: Introductionmentioning
confidence: 99%